Preconditioning optimization of hydraulic fracturing in block caving of hard rock mass - Min, Huang; Sijie, Cai; Mingqing, Huang; Xiaojun, Wang (Frontiers in Earth Science, 2023)
Cavability tends to be poor in hard rock mines mined by block caving mining method. Hydraulic fracturing is a promising preconditioning technology for hard rock masses, and the preconditioning effect is subject to variable parameters. The influence of cluster number, injecting rate and liquid volume on fracture propagation is studied with onsite practice of hydraulic fracturing. The fracability is firstly verified by true triaxial fracturing test, preconditioning parameters are secondly optimized with numerical simulation, and then the optimized on-site construction was monitored using electromagnetic monitored method. The results show that the fracture radius is negatively correlated with the number of clusters, and gradually decreases with the increase of the number of clusters. However, the fracture weakening area increases with the increase of cluster number. The fracture weakening area increases with the increase of injecting rate. In addition, the fracture radius increases firstly and then decreases. The fracture weakening area and fracture radius increase with the increase of liquid volume. The optimized parameters are: 4 clusters, injecting rate is 4m 3 /min, and liquid volume is 500m 3 . On this basis, on-site experiments were conducted and monitored through electromagnetic methods. The monitored results showed that the optimized parameters can effectively achieve the expansion of hydraulic fracturing and achieve the goal of weakening hard rock.